VARIASI BENTUK DAN FUNGSI MADIHIN (VARIATIONS IN FORM AND FUNCTION OF MADIHIN) - Ahmad Fauzan (Universitas Lambung Mangkurat, 2022)
Variations in Form and Function of Madihin. This research aims to (1) describe the variations and development in form of madihin and (2) describe the variations and development in function of madihin. Approach used in this research is qualitative and descriptive method. Sources of data in this research are madihin video recordings and informants. Data collection technique used triangulation. Technical data analysis is content analysis and models of Miles and Huberman, is data reduction, data presentation, and drawing conclusions or verification. Research result showed that (1) concerning form of madihin is (a) language variations indicate dominance of a particular language and development is used of Indonesian and foreign languages, (b) rhyme patterns variations indicate amount patterns used and development of varied forms, (c) serving structure variations indicate amount different structure used and development of varied forms, (2) concerning variations in function of madihin is (a) traditional madihin contain function of entertainment or humor, education, satire, and Islamic preaching, (b) dangdut madihin contain function of marriage and promotion (entertainment services), (c) instagram madihin contain function of campaign (environment), promotions (products, campuses, and tourist attractions), birthday greetings, and appeal, and (d) beatbox madihin contain function of solidarity or humanity and campaigns (regional head candidates). Concerning its development is (a) promotional functions (entertainment services, products, campuses and tourist attractions), (b) campaign (environment and regional head candidates), (c) birthday greeting, and (d) appeal.Key words: variations in form, variations in function, development in form, development in function, madihinVariasi Bentuk dan Fungsi Madihin. Penelitian ini bertujuan untuk (1) mendeskripsikan variasi serta perkembangan bentuk madihin dan (2) mendeskripsikan variasi serta perkembangan fungsi madihin. Pendekatan yang digunakan dalam penelitian ini ialah kualitatif dan dengan metode deskriptif. Sumber data dalam penelitian ini ialah rekaman video madihin dan informan. Teknik pengumpulan data menggunakan triangulasi. Teknik analisis data ialah analisis isi dan model Miles dan Huberman, yakni reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa (1) menyangkut bentuk madihin yakni (a) variasi bahasa menunjukkan kedominanan bahasa tertentu dan perkembangannya ialah penggunaan bahasa Indonesia dan asing, (b) variasi pola sajak menunjukkan jumlah pola yang digunakan dan perkembangannya bentuk yang variatif, (c) variasi struktur penyajian menunjukkan perbedaan jumlah struktur yang digunakan dan perkembangannya bentuk yang variatif, (2) menyangkut variasi fungsi madihin meliputi (a) madihin tradisional memuat fungsi hiburan atau humor, pendidikan, sindiran, dan dakwah Islam, (b) madihin dangdut memuat fungsi perkawinan dan promosi (jasa hiburan), (c) madihin instagram memuat fungsi kampanye (lingkungan), promosi (produk, kampus, dan tempat wisata), ucapan hari lahir, dan imbauan, serta (d) madihin beatbox memuat fungsi solidaritas atau kemanusiaan dan kampanye (calon kepala daerah). Menyangkut dengan perkembangannya meliputi (a) fungsi promosi (jasa hiburan, produk, kampus, dan tempat wisata), (b) kampanye (lingkungan dan calon kepala daerah), (c) ucapan hari lahir, dan (d) imbauan.Kata-kata Kunci: variasi bentuk, variasi fungsi, perkembangan bentuk, perkembangan fungsi, madihin